KAJIAN NARASI FOTO TRADISI DAN BUDAYA ETNIS TIONGHOA PADA TITD DI BALI SEBAGAI REPRESENTASI HARMONI DALAM MULTIKULTURALISME - Surya Dinata, Ramanda Dimas; Hendrawan, Freddy; Pratama, I Gede Yudha; Septiani Dewi, Ni Made Diah (Universitas Mercu Buana, 2024)
The notion of multiculturalism is conceived as an idea to acknowledge and accommodate diversity and differences in beliefs, practices, traditions, languages, or lifestyles. However, the understanding of the notion of multiculturalism is limited to the recognition of cultural diversity possessed by certain individuals or groups. During the intercultural interactions in urban society that occur dynamically, hybridity has become an important capital for being to live side by side and have the ability to be renewed. This hybridity phenomenon has been recorded through photographs of traditional and cultural activities of the Chinese ethnic group at the Tri Dharma Temples in Bali. The practice of Chinese ethnic traditions and culture in Bali is an effort by the Chinese-Balinese ethnic group to preserve their ancestral heritage by adopting Balinese cultural elements. As a work of art that embodies narrative function, photographs of traditional and cultural activities of the Chinese ethnic group at the Tri Dharma Temples in Bali conveyed stories and connected several events within the framework of the concept of multiculturalism. This qualitative descriptive research aimed to document the traditional and cultural activities of the Chinese ethnic group at the Tri Dharma temples in Bali using a combination of photo-ethnography and narrative research designs.The narrative of photographs within this study provided a visual that described stories about minority groups of migrant cultures in indexical, iconic, and symbolic forms. The occurred events implemented the concept of multiculturalism and reflected aspects of religion, socio-culture, economics, art and design. This study provides a concrete picture of how diversity and cultural differences are not only recognized and accommodated, yet, also how minority groups can maintain and express their cultural identity amidst diversity and cultural differences.